2003
DOI: 10.1183/09031936.03.02582001
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial asthma causing symptoms suggestive of angina pectoris

Abstract: Many patients undergoing pharmacological stress echocardiography for assessing symptoms suggestive of coronary artery disease are found to have a normal test. This study was performed to evaluate whether asthma symptoms simulate angina pectoris.A total 41 consecutive patients who had a negative pharmacological stress echocardiography and had been evaluated for angina pectoris were studied. Patients with previously known coronary artery disease or obstructive lung disease were excluded. Lung function testing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
7
0
2
Order By: Relevance
“…Later it has been confirmed that Rose angina may represent bronchial asthma 18. Rose angina was linked with lung symptoms and increased mortality from pulmonary disease in our cohort, although the absolute mortality from this cause was modest.…”
Section: Discussionsupporting
confidence: 72%
“…Later it has been confirmed that Rose angina may represent bronchial asthma 18. Rose angina was linked with lung symptoms and increased mortality from pulmonary disease in our cohort, although the absolute mortality from this cause was modest.…”
Section: Discussionsupporting
confidence: 72%
“…Chronic bronchitis, bronchial asthma, pulmonary disease and symptoms, depression, anxiety and non-cardiac pain may be reasons for positive RAQ outcomes (22–25). Nevertheless, Graff-Iversen et al (24) found that a 3-item version of the RAQ predicted mortality from ischaemic heart disease (IHD) in Norwegian women and men aged 40–49 years.…”
Section: Discussionmentioning
confidence: 99%
“…Geoffrey Rose noted that the diagnosis of angina presents special problems in populations with a high prevalence of chronic bronchitis,1 and overlap has also been found with asthma 20. In a cross-sectional survey data of men (n=30 658) and women (n=35 733) aged 40–42 years, we found that Rose angina was associated with asthma, anxiousness, depressive complaints, musculoskeletal pain and overweight,21 indicating confounding factors that are hard to fully account for.…”
Section: Discussionmentioning
confidence: 73%